Combined Unit for Tillage with Pulsed Shock Wave Action - B. Kh. Akhalaya; Yu. S. Tsench (Сельскохозяйственные машины и технологии, 2023)
The paper shows that incorporating a multifunctional combined unit with pulsed shock wave action into soil tillage presents a pertinent and promising advancement in the soil cultivation system. (Research purpose) The research aims to develop a multifunctional combined unit for soil tillage integrating pulsed shock wave action. The objectives include enhancing productivity, refining tillage quality and promoting ecological considerations. (Materials and methods) The unit consists of a main frame, two side-folding sections, and a central section, which is made featuring a carriage, support and transport wheels. Additionally, it incorporates a frame in the shape of a hollow shaft, connected to a compressed air cylinder. The front frames of each section are equipped with rigidly fixed working bodies taking the form of cultivator paws with embedded pneumatic tubes. These tubes have outlet holes positioned at the ends of the wings of the paws, with a compressed air effective radius of 5-10 centimeters. (Results and discussion) The established ratio between the depth of surface tillage using a cultivator paw and the depth of subsoil tillage through pulsed blows of compressed air is 1:2. The tillage devices are supplemented by disc cutters with a diameter ranging from 25 to 30 centimeters, along with harrows designed for processing to a depth of 5-7 centimeters. (Conclusions) Enhanced by this modification, the design of the multifunctional combined unit enables the simultaneous execution of multiple operations, including cultivation with weed destruction, soil loosening using high-pressure air flow, and surface milling and grinding.